Pengembangan Audio Guide sebagai Aksesibilitas Informasi bagi Penyandang Disabilitas Netra di Perpustakaan Umum - Fauziyah, Wahyu Dirga; Inawati, Inawati (BACA: Jurnal Dokumentasi dan Informasi, 2025)
The Malang City Public Library provides special services for visually impaired library users through the Braille Corner Service (LAPOBRA), which is equipped with a braille collection and guiding blocks. However, the use of LAPOBRA has not been optimal due to a lack of mobility support facilities for visually impaired library users. The problem identified in this study is the absence of easily accessible guidance media for these users. Therefore, the development of an audio guide could serve as a valuable resource to help visually impaired library users access LAPOBRA, as this product has not yet been implemented at the Malang City Public Library. The purpose of this study is to develop an audio-based user guide as a means of educating users to improve the effectiveness of LAPOBRA orientation and accessibility. This study employs the Research and Development method with the Borg & Gall model approach, which is simplified into seven stages: research and data collection, planning, product development, initial testing, product revision, field testing, and final revision. Data were collected through observation, interviews, case studies, and questionnaires from six visually impaired library users selected through random sampling. The testing stage was conducted by media experts, subject matter experts, and visually impaired library users. The result of this research is an audio guide integrated with guiding blocks to assist visually impaired library users in accessing LAPOBRA. This audio guide explains the process of entering and exiting the service area based on the average footstep measurements of Indonesians. The results of the field test indicated a very high validity rate of 94%, demonstrating that this product is highly suitable for use. The creation of this product facilitates independent access to LAPOBRA for visually impaired library users and enhances their mobility in obtaining information.